Diversidade e composição de formigas Ponerines (Hymenoptera, Formicidae, Ponerinae) de Serapilheira na Estação Científica Ferreira Penna, Caxiuanã, Melgaço, Pará, Brasil - BASTOS, Alexandro Herbert dos Santos (Universidade Federal do Pará, 2013)
The ponerines, after myrmicines, are the most conspicuous, rich and abundant ground-dwelling ants from tropical rain forests. In this ecosystem the ponerines are ecologically important, since they prey many kinds of invertebrates and nest among leaf litter and rotten logs. In this work the range of leaf litter Ponerinae ants was studied, as well their abundance, richness, diversity, and species composition. In addition, how the litter quantity affect the ponerines range was analyzed. This study was carried out in six primary Amazonian forest areas of 1 Km² (Area I, II, III, IV, V, and VI) at Ferreira Penna Scientific Station (ECFPn), Caxiuanã, Melgaço, Pará state, Brazil. The material was collected at April and October of 2003, and January of 2004, following the Ants Monitoring Protocol of TEAM Iniciative/Caxiuanã Project for the study of leaf litter ants. In each sampled site four transects lines of 100 m (sample units) with 10 samplings points were established. At each sampling point of 1 m², the leaf litter samples were sifted and then placed in mini-Winkler sacks. A total of 4,031 specimens were collected, belonging to three tribes, eight genera, and 60 species of Ponerinae in 470 records. In average 6.52 species were collected per sample. The total richness was estimated in 81 species using first order Jackkinife method. Hypoponera was the most abundant and rich genus, with 22 species in 268 records. The genus Hypoponera plus Pachycondyla showed a strong numerical dominance, with more than 70% of collected species. The Area V was the most diverse (H=3.30), with the highest species richness (38) and abundance (121 records), as well as with the largest amount of leaf litter (ANOVA; p<0,05 between Area V and the other sites). The quantity of leaf litter affected positively the ponerines ants species abundance and richness, and also influenced the species composition. The most common species were: Hypoponera sp#1, Hypoponera sp#2, Hypoponera sp#6, Hypoponera sp#7, Odontomachus scalptus and Pachycondyla constricta. These few species (10%) yielded more than half of total abundance. In short, the ponerines were widely spread in the leaf litter of ECFPn primary forests, being numerically affected by leaf litter volume. The sites showed differences in species diversity, abundance and richness. Furthermore, the species composition of ponerines ants at nearby samples often presented low similarity once high number of species was rare. Thus, the leaf litter availability of Amazonian forest is a key role on species distribution, even at small scales.